Penerapan Kemandirian Ekonomi dalam Mengembangkan Peran Anggota Organisasi Aisyiyah Ranting Ngadiwinatan - Rahmah; Afsah, Yusi Riwayatul (DHARMA BAKTI, 2022)
Aisyiyah as a religious women's organization in Ngadiwinatan has various activitiesbased on community empowerment－one of them is empowering the economicindependence of Aisyiyah residents. During this pandemic, Aisyiyah's work from theNgadiwinatan Branch of Aisyiyah is urgently needed to help Aisyiyah residents who areaffected by economic difficulties, especially in maintaining economic independence.Therefore, it takes an effort to be able to facilitate or help the economic difficulties of theresidents of Aisyiyah Ngadiwinatan. The ultimate goal of this activity is to optimize the roleof the Ngadiwinatan Branch in the economic independence of its members. This activityconsists of three stages, starting with an entrepreneurship seminar, creating an onlinediscussion forum and facilitating the opening of the Aisyiyah Ngadiwinatan Branch ofeconomic business unit. The results of this activity are the increased knowledge ofparticipants in entrepreneurship, the active involvement of members in online shops and theformation of the BUEKA Ngadiwinatan shop manager as a forum for the economicindependence of Aisyiyah Ngadiwinatan residents. Furthermore, the implication of thisactivity is the increased insight of the participants to develop their business online byutilizing social media and working together. The conclusion of this activity is that the activeparticipation and high motivation of the administrators and members of the Ngadiwinatanbranch of Aisyiyah led to the immediate formation of an economic business unit named theBUEKA Ngadiwinatan shop.